Uncovering identity in mortuary analysis : community-sensitive methods for identifying group affiliation in historical cemeteries - Heilen, Michael (Statistical Research, Inc., 2012)
This volume presents a sophisticated set of archival, forensic, and excavation methods to identify both individuals and group affiliations - cultural, religious, and organizational - in a multiethnic historical cemetery. Based on an extensive excavation project of more than 1,000 nineteenth-century burials in downtown Tucson, Arizona, the team of historians, archaeologists, biological anthropologists, and community researchers created an effective methodology for use at other historical-period sites. Comparisons made with other excavated cemeteries strengthens the power of this toolkit.